Instrumented gait analysis post‐anterior cruciate ligament reconstruction in pediatric patients: A non‐invasive method for quantifying the static and dynamic leg axis - Leonie Kijewski; Eva Böker; Karoline Hofmann; Thomas Engel; Pierre Hepp; Maren Witt (Journal of Experimental Orthopaedics)
Abstract Purpose This study explores the potential of Instrumented gait analysis (IGA) as a non‐invasive tool for monitoring rehabilitation in pediatric patients with anterior cruciate ligament (ACL) injuries. Current clinical assessments, such as physical exams and X‐rays, have limitations in evaluating dynamic knee alignment and loading. IGA may offer a more precise method to track rehabilitation progress and detect altered gait biomechanics following ACL reconstruction (ACLR). We hypothesize that IGA can provide insights into differences in frontal knee alignment and mechanical loading between static and dynamic conditions in pediatric patients following ACLR. Methods IGA was conducted on 18 patients (mean age: 15 ± 2 years) at 3 and 12 months following ACLR, and seven conservatively treated patients (mean age: 12 ± 3) at 12 months post‐injury. Retroreflective markers were placed using the CAST lower body model. The gait was recorded in 3D using 12 infrared and two video cameras. Ground reaction forces were measured with force plates. Frontal knee alignment was assessed from kinematic data at four gait events: double‐limb stance, initial contact, loading response, and mid‐stance, identified by C‐Motion Visual3D Professional. Frontal knee joint moments were calculated based on inverse kinematic and dynamic in Newton‐meters per kilogram (Nm/kg) at the specified gait events. Repeated‐measures ANOVA was used to compare frontal knee alignment between static and dynamic conditions, while paired t‐tests assessed differences between injured and uninjured extremities. Results In the surgical group, a significant increase in body height occurred between 3 and 12 months (p = 0.001) without notable changes in the static or dynamic frontal axis (p > 0.05). At 12 months post‐surgery, mean frontal knee alignment differed significantly between gait events (p < 0.001), showing a transition from valgus during stance to a nearly neutral axis during loading response. A significant difference was observed at initial contact, where the affected leg remained in greater valgus than the unaffected side (p = 0.026). Joint moments showed no significant differences between the healthy and affected sides (p > 0.05). No significant differences were found between the surgical and conservative groups. Conclusions The findings of this study suggest that IGA can detect dynamic alignment deviations, supporting its potential as a complementary tool for monitoring knee function following pediatric ACL injuries. The absence of significant alignment changes over time indicates a low risk of surgery‐induced growth plate injury. While IGA may help identify alignment‐related risk factors for re‐rupture, its ability to accurately predict graft insufficiency remains unclear. Level of Evidence Level II, prospective cohort study.